A Reduction in Undergraduate Misconceptions on AC Circuits through Interactive Simulations - Pratama, Defrianto (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2025)
Misconceptions are a major barrier in physics learning, particularly in abstract concepts such as alternating current (AC). This study aimed to reduce the number of students experiencing misconceptions on AC topics through PhET-assisted learning. The method used was a quasi-experimental one-group pretest-posttest design, involving 152 Electrical Engineering students enrolled in an Applied Physics course. The instrument employed was a four-tier test developed for six key AC concepts. Pretest results showed that 32.1% of students on average experienced misconceptions, with the highest found in the concept of resonance (50.0%). After instruction using PhET simulations, the average misconception rate dropped to 7.8%, with an average reduction of 24.3%. McNemar's test confirmed that the reduction was statistically significant (p < 0.05) across all concepts. PhET simulations proved effective by providing dynamic visualizations, enabling interactive exploration, and triggering cognitive dissonance that encourages conceptual revision. This study recommends the integration of interactive simulations in physics instruction, especially for abstract and dynamic topics.